Economic evaluation of fertilization strategies in cool season annual forage grasses in the Pampeana Semiarid Region (Semiárida, 2024)
Cool season annual forage grasses biomass production and derived meat production can be affected if they are not fertilized. Based on biomass production from different levels of nitrogen fertilization it is proposed to carry out an economic analysis from different methodological approaches, linked to each other. First, the effect on implantation cost and on the unit cost (CU) of dry matter was assessed. The economic gain was calculated for additional meat production, and finally a threshold was established of an input-output relationship (RIP) indicator looking for the feasibility of fertilizing with economic criteria. Production data from a trial carried out at Anguil, La Pampa, including 9 cultivars of 4 species and with 3 levels of fertilization were used for economic analysis carried out based on the evolution of prices within three periods of a 10-years long series. Relative prices and implantation costs of each period influence the CU of the forage production. The economic viability of fertilization is reached when the initial productivity is lower and the response to fertilizer is higher. The agronomic efficiency is higher than the RIP for 70 to 80 % of the treatments, so it is feasible to fertilize with economic criteria.
Keywords: planting costs; economic feasibility; input-output relationship